Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

G(x) = 8x - 9 for g(x) = 23

Sagot :

23=8x-9 It’s says g(x)=23 so put 23 where
+9 +9. The g(x) is on the equation.
First, add the 9
32=8x
/8 /8. Then, divide by 8.

4=x. And this should be your answer

Hope this helps! :)